Career Exploration and Career Decision Self-Efficacy in Northwest Chinese Pre-service Kindergarten Teachers: The Mediating Role of Work Volition and Career Adaptability - Zhao, Fangfang; Li, Ping; Chen, Siyuan; Hao, Yijun; Qin, Jinliang (Frontiers in Psychology, 2022)
Studies have documented that career exploration is significantly associated with CDSE, but how this association occurred is not clear yet. This study committed to clarify the mechanism underlying the relationship between career exploration and CDSE by investigating the mediation effect of work volition and career adaptability among 586 preservice kindergarten teachers. The participants are recruited from Ningxia Hui Autonomous Region in Northwest China, covering Han, Hui and other minorities. They took part in a two-wave (six months apart) longitudinal survey and reported on their career exploration at T1, work volition, career adaptability, and career decision self-efficacy at T2. Results showed that T1 career exploration directly related to the T2 career decision self-efficacy. Further, career exploration contributed to the career decision self-efficacy through both the separated mediation path and the chained mediation path of T2 work volition and T2 career adaptability. The results suggest that individuals who engage in more career exploration activities are likely to have more confidence in their abilities to make career decision over time, which was partially and serially explained by individuals’ perception of capacity despite constraints and greater self-regulatory strength. This study is a first attempt to deeply clarify the link between career exploration and career decision self-efficacy, the findings shed light on the independent and serial mediating effects of work volition and career adaptability. The implications and limitations are discussed.